2012
DOI: 10.1080/09540121.2012.701714
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic and behavioral correlates for HIV and syphilis infections among migrant men who have sex with men in Beijing, China

Abstract: Migrant men who have sex with men (MSM) may be particularly vulnerable to sexually transmitted infections (STIs) including HIV. This study examines the rates of HIV and syphilis infections and associated socio-demographic and behavioral factors among migrant MSM in China. Data from 307 migrant MSM were collected in Beijing, China. Blood specimens were collected to test for HIV and syphilis infections. HIV and syphilis rates were 5.9% and 20.2%, respectively. Multivariate logistic regression analyses showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 27 publications
2
37
3
Order By: Relevance
“…In contrast, the MSM in our study living in Beijing for fewer years or without Beijing 'Hukou' were more likely to frequent non- † Includes: beach, woods, street, theater, public transportation, hotel and private homes Internet venues. This subgroup might include a majority of transient workers (migrants) from village/township/country level cities to large cities for better employment opportunities and living condition [44,45]. These marginal population might be less educated and faced financial constraints [44], both barriers to the conduct of online sexfinding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the MSM in our study living in Beijing for fewer years or without Beijing 'Hukou' were more likely to frequent non- † Includes: beach, woods, street, theater, public transportation, hotel and private homes Internet venues. This subgroup might include a majority of transient workers (migrants) from village/township/country level cities to large cities for better employment opportunities and living condition [44,45]. These marginal population might be less educated and faced financial constraints [44], both barriers to the conduct of online sexfinding.…”
Section: Discussionmentioning
confidence: 99%
“…This subgroup might include a majority of transient workers (migrants) from village/township/country level cities to large cities for better employment opportunities and living condition [44,45]. These marginal population might be less educated and faced financial constraints [44], both barriers to the conduct of online sexfinding. MSM who were unemployed or retired also tended to visit traditional venues to find sex.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in Beijing showed that migrant population were low in socio-economic status and were limited in knowledge of HIV and benefit of timely HIV diagnosis. 58,62 Interventions to increase frequency of HIV testing should focus on transient residents.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous research among MSM in Beijing revealed that with the increasing epidemic of HIV among MSM in recent years, the number of migrants among recruited participants also showed a noticeable upward trend 1011 This phenomenon implies the following: (1) migrant MSM play a major role in MSM society in Beijing; (2) this marginal population has emerged gradually with the constant improvement in sampling methods; and (3) studies more targeted on the particular population are urgently needed, since currently only a few cross-sectional studies have been conducted to investigate HIV/STD infections and relative risk factors in this group 2122 Thus, the purpose of this research was to assess the incidence of HIV and syphilis and examine the predictors associated with seroconversion and retention in a prospective cohort study among migrant MSM in Beijing, China.…”
Section: Introductionmentioning
confidence: 99%